Catatonia with Psychosis in an 8-Year-Old Child: A Case Report and a Literature Review - Weiss, Margaret D.; Schibuk, Larry; Gokarakonda, Srinivasa B.; Henderson, Renea; Esmaeilpour, Dianna (Case Reports in Psychiatry, 2022)
Objective. We present a narrative review of pediatric catatonia and a case report illustrating the complexity of management of psychosis in a child with catatonia. Method. The literature search used the text terms pediatric, catatonia, and antipsychotics and the search engines PubMed and EBSCO. All references from peer-reviewed journals were reviewed for treatment strategies specific to management in children who are also psychotic. Findings. This 8-year-old girl presented with psychotic symptoms which were initially treated with antipsychotics and evolved into life-threatening catatonia that was eventually stabilized with a total daily dose of 46 mg of lorazepam. Lower doses led to recurrence. Once catatonia improved, she tolerated combined benzodiazepine and antipsychotic treatment. Long-term maintenance over 5 years required maintenance treatment with both benzodiazepines and antipsychotics to prevent relapse. Conclusions. The extraordinary doses of benzodiazepines found to be optimal for management of catatonia in this child led to improved alertness and orientation, without evident sedation. Catatonia did not recur with later management of psychosis using neuroleptics when added to lorazepam. The current literature on pediatric catatonia does not provide guidance on dose maintenance or when and if to rechallenge with antipsychotics.